Compare and analyse marketing strategies using consumer focused studies. The case of TomTom vs. Garmin - Stefanova, Antonia (2014)
The following dissertation paper focuses on a central research question that is to compare and appraise strategic marketing activities of a first mover navigation organisation, TomTom B.V., to its most prominent competitor Garmin Ltd, a successful follower. The intense situation in the global positioning systems market provides a great possibility of investigating the two giant organisations' internal environment, competitive environment and customers' purchase behaviour. In this regard, marketing strategies will help at explaining and analysing how both organisations develop and implement sustained competitive advantages, strategies for competitive advantage, competitive approaches and branding strategies. For this purpose, in-depth qualitative research will be conducted on TomTom's marketing managers and on TomTom's and Garmin's customers. The first type of research shall look into the company's resources and capabilities, competitive goals and knowledge about the competition. The latter, in the form of consumer focused studies, shall serve as a feedback of how successful the implemented strategies and approaches of both firms are. The research paper is based on the conceptual analysis of relevant strategic marketing and consumer behaviour theories and models, detailed investigation of the organisations' cases and on the results of the two qualitative studies. On this matter, three company's interviews and eight, four per organisation, consumers' interviews were conducted for data collection and analysis. The interpretivist philosophical approach and narrative analysis were applied in the research in order to gather 'stories' about the interviewees' perceptions, opinions and experiences. Based on these results, a discussion about both organisations' core strategies will be given. Recommendations and implications about TomTom's business will be provided.